Cement-based grouting material and preparation method thereof
A ternary cementitious system is formed by using a specific ratio of high-belite sulfoaluminate cement, anhydrite powder, and slag powder. Combined with accelerators and retarders, it solves the problems of insufficient strength and low construction efficiency of traditional cement-based grouting materials under high water-to-material ratios, achieving improved high fluidity, early strength, and later compressive strength, and is suitable for semi-flexible pavement construction.
Patent Information
- Application Number
- CN202511033939.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-25
- Publication Date
- 2025-11-18
AI Technical Summary
Traditional cement-based grouting materials suffer from low bonding strength, insufficient flexural and compressive strength, poor tensile bonding performance, decreased wear resistance, and increased shrinkage deformation due to excessively low water-to-material ratio. Furthermore, they are characterized by low construction efficiency, high cost, small paving area, and difficulty in ensuring road surface smoothness.
Using a specific ratio of crack-resistant, fast-setting, and quick-hardening high-belite sulfoaluminate cement, anhydrite powder, and slag powder as the core cementitious materials, combined with graded fine aggregates and functional admixtures, a ternary cementitious system is formed to optimize fluidity and homogeneity. Through the combination of accelerators and retarders, high fluidity and rapid solidification under high water-to-material ratio are achieved, forming a nano-scale ettringite whisker structure and improving early and late strength.
Achieving high fluidity and high strength with a high water-to-material ratio improves construction efficiency, reduces costs, ensures road surface smoothness and wear resistance, enhances resistance to dynamic loads, and extends service life.
Smart Images

Figure BDA0005518150250000051 
Figure BDA0005518150250000071 
Figure BDA0005518150250000081
Abstract
Description
Technical Field
[0001] This application relates to the technical field of building materials, specifically to a cement-based grouting material and its preparation method. Background Technology
[0002] Traditional cement-based grouting materials are limited by their cementitious system. To ensure necessary strength properties, their water-to-material ratio (the mass ratio of water to all solid materials) is usually strictly limited to below 0.30. Once the water-to-material ratio exceeds this limit, the grout will inevitably suffer from a series of serious defects due to reduced density and loose structure, such as low bond strength, insufficient flexural and compressive strength, poor tensile bond performance, decreased abrasion resistance, and increased shrinkage deformation. However, while using an excessively low water-to-material ratio can achieve relatively good physical properties, it brings significant drawbacks in actual engineering, such as small paving area per unit area, high overall cost, low construction efficiency, and difficulty in guaranteeing the final road surface smoothness. Summary of the Invention
[0003] To address the core problem of existing technologies that struggle to balance strength performance and ease of construction under high water-to-material ratios, this application provides a cement-based grouting material and its preparation method.
[0004] The primary objective of this application is to provide a high-water-strength cement-based grouting material powder specifically designed for semi-flexible pavements. This powder uses a specific ratio of crack-resistant, fast-setting, and quick-hardening high-belite sulfoaluminate cement, anhydrite powder, and slag powder as core binders, aiming to overcome practical engineering problems in existing technologies where the water-to-material ratio is too low due to limitations in the binder system, resulting in small paving area, high overall cost, low construction efficiency, and difficulty in ensuring pavement smoothness. The secondary objective of this application is to provide a simple and easy-to-use method for preparing high-water-strength cement grouting materials for on-site construction.
[0005] In a first aspect, this application provides a cement-based grouting material, specifically comprising the following components in parts by weight: 25.2–35.0 parts of high-belite sulfoaluminate cement, 4.32–6.32 parts of anhydrite powder, 6.48–19.46 parts of slag powder, 0–14.92 parts of heavy calcium carbonate powder, 46.92–47.38 parts of graded fine aggregate, 0.02–0.05 parts of water-reducing agent, 0–0.6 parts of thickener, 0.03–0.2 parts of defoamer, 0–0.17 parts of cellulose, 1.0–2.5 parts of latex powder, 0.03–0.1 parts of retarder, and 0.03–0.2 parts of accelerator; the water-to-material ratio is 0.30–0.43; the accelerator is prepared from calcium carbonate, alumina, and ethylene-vinyl acetate copolymer.
[0006] The cement-based grouting material provided in this application has significant advantages, particularly meeting the stringent requirements of semi-flexible pavements: First, it is based on a ternary cementitious system composed of crack-resistant, fast-setting, and quick-hardening high-belite sulfoaluminate cement, anhydrite powder, and slag powder in a specific ratio. This ternary system is the material basis for generating nano-sized ettringite whiskers and achieving high water content and high strength. The ratio range has been optimized experimentally; exceeding this range prevents the formation of a dense structure under high water content (e.g., excessive slag results in insufficient early strength). Under high water conditions, C4A3S, CaSO4, Al2O3, and CaO react rapidly, rapidly nucleating and generating approximately 10-nanometer-scale ettringite (AFt) crystals. These nano-sized ettringite whiskers continue to increase with the reaction, freely dispersing and densely filling the framework and capillary pores, forming a high-strength structure. In contrast, ordinary silicate cement or traditional sulfoaluminate cement systems generate approximately 1-micrometer-sized ettringite crystals under high water conditions, failing to achieve the nano-filling effect and resulting in insufficient strength.
[0007] Secondly, the ternary cementitious system, along with graded fine aggregates and functional admixtures (water-reducing agent, cellulose, thickener, latex powder, retarder, and accelerator), optimizes the fluidity and homogeneity of the grout under high water conditions. The water-reducing agent ensures high fluidity; the defoamer eliminates air bubbles and improves density; the latex powder enhances bond strength and toughness; the thickener, cellulose, and latex powder synergistically improve tensile bond strength, ductility, and abrasion resistance; the retarder and accelerator precisely control the setting time, improving construction fluidity and mechanical properties. The synergistic combination of multiple components enables the grouting material to achieve excellent high fluidity even at a water-to-material ratio as high as 0.31–0.43, facilitating efficient construction and penetration filling of porous asphalt skeletons. Simultaneously, this material exhibits excellent early and late flexural and compressive strength.
[0008] Ultimately, the high-water-strength cement grouting material provided in this application exhibits excellent high fluidity within a wide water-to-material ratio range of 0.31 to 0.43 and can solidify rapidly, ensuring the rapid formation of an effective load-bearing layer on the construction surface. More importantly, it demonstrates excellent performance in rapidly developing early strength and significantly improving later compressive and flexural strength, and this cement-based grouting material also possesses excellent low shrinkage and abrasion resistance.
[0009] Preferably, the cement-based grouting material specifically comprises the following components in parts by weight: 27.2–32.0 parts of high-belite sulfoaluminate cement, 4.82–5.82 parts of anhydrite powder, 11.48–14.46 parts of slag powder, 5–9 parts of heavy calcium carbonate powder, 46.92–47.38 parts of graded fine aggregate, 0.03–0.04 parts of water-reducing agent, 0.2–0.4 parts of thickener, 0.09–0.14 parts of defoamer, 0.06–0.12 parts of cellulose, 1.5–2.0 parts of latex powder, 0.06–0.08 parts of retarder, and 0.12–0.18 parts of accelerator; the water-to-material ratio is 0.34–0.38.
[0010] Preferably, the high-belite sulfoaluminate cement is selected from any one of white crack-resistant, fast-setting, and fast-hardening high-belite sulfoaluminate cement, crack-resistant, fast-setting, and fast-hardening high-belite sulfoaluminate cement, and high-strength, fast-setting, and fast-hardening high-belite sulfoaluminate cement. When the requirement for a non-white cement-based grouting material is not met, crack-resistant, fast-setting, and fast-hardening or high-strength, fast-setting, and fast-hardening high-belite sulfoaluminate cement can be used to replace the white variety.
[0011] Preferably, the graded fine aggregate is composed of a mixture of 80-120 mesh dolomite sand and 20-60 mesh dolomite sand in a weight ratio of 1.5-2.5:0.5-1.5.
[0012] Preferably, the graded fine aggregate is composed of a mixture of 80-120 mesh dolomite sand and 20-60 mesh dolomite sand in a weight ratio of 1.7-2.2:0.7-1.2.
[0013] Experimental analysis shows that the graded fine aggregate composed of 80-120 mesh dolomite sand and 20-60 mesh dolomite sand in a weight ratio of 1.7-2.2:0.7-1.2 can further improve the performance of cement-based grouting materials.
[0014] Preferably, the preparation method of the coagulant is as follows: calcium carbonate and alumina are mixed and stirred to obtain a solid material, 8-12% distilled water is added and stirred thoroughly, then ethylene-vinyl acetate copolymer is added and stirred thoroughly, and the mixture is kept under a pressure of 30-50 kN for 25-50 s, then dried to constant weight, and ball-milled to obtain the final product.
[0015] Preferably, in the preparation method of the coagulant, the weight ratio of calcium carbonate, alumina, and ethylene-vinyl acetate copolymer is 2-3:7-11:0.2-1.2.
[0016] Preferably, in the preparation method of the coagulant, the weight ratio of calcium carbonate, alumina, and ethylene-vinyl acetate copolymer is 2.2-2.8:8-10:0.5-0.9.
[0017] In one specific embodiment, in the preparation method of the coagulant, the weight ratio of calcium carbonate, alumina, and ethylene-vinyl acetate copolymer can be 2.2:8:0.5, 2.5:8:0.5, 2.8:8:0.5, 2.2:9:0.5, 2.5:9:0.5, 2.8:9:0.5, 2.2:10:0.5, 2.5:10:0.5, 2.8:10:0.5, 2.2:8:0.7, 2.5:8:0.7, 2. 8:8:0.7, 2.2:9:0.7, 2.5:9:0.7, 2.8:9:0.7, 2.2:10:0.7, 2.5:10:0.7, 2.8:10:0.7, 2.2:8:0.9, 2.5:8:0.9, 2.8:8:0.9, 2.2:9:0.9, 2.5:9:0.9, 2.8:9:0.9, 2.2:10:0.9, 2.5:10:0.9, 2.8:10:0.9.
[0018] Experimental analysis shows that by controlling the weight ratio of calcium carbonate, alumina, and ethylene-vinyl acetate copolymer within the above-mentioned range, the performance of cement-based grouting materials can be further improved.
[0019] Preferably, the performance parameters of the ethylene-vinyl acetate copolymer are: vinyl acetate content of 25-30 wt% and melt index of 15-30 g / 10 min.
[0020] Preferably, the water-reducing agent is a polycarboxylate superplasticizer; the thickener is HPMC; the defoamer is German Mingling P803 defoamer AGITAN powder defoamer; the cellulose is hydroxyethyl cellulose; the latex powder is VAE powder; and the retarder is selected from one or more of sodium gluconate and tartaric acid.
[0021] Secondly, this application provides a method for preparing the cement-based grouting material, which specifically includes the following steps in sequence: weighing the corresponding weights of each raw material component, mixing high-belite sulfoaluminate cement, anhydrite powder, slag powder, heavy calcium carbonate powder, graded fine aggregate, water-reducing agent, thickener, defoamer, cellulose, latex powder, retarder, and accelerator evenly to obtain dry powder material; adding water and mixing evenly to obtain the cement-based grouting material.
[0022] In summary, the technical solution of this application has the following effects: The technical solution provided in this application achieves excellent high fluidity and workability, early and late strength, excellent volume stability (low shrinkage, high adhesion) and significant overall cost-effectiveness under high water-to-material ratio conditions. It solves the core problems of traditional high-strength grouting materials, such as small paving area, high cost, low efficiency and poor flatness caused by low water-to-material ratio.
[0023] The cement-based grouting material provided in this application achieves high strength under a high water-to-material ratio, significantly improves material utilization efficiency, and reduces overall costs: (1) Significantly increases paving area: When more water is added to the same mass of dry powder, the resulting grout volume is larger, and a single mixing can cover a larger construction area. (2) Directly reduces material costs: Less dry powder is required to achieve the same construction volume (coverage area), directly saving the most important raw material costs. (3) Improves construction efficiency: The increased coverage area per mixing reduces the number of mixing times and the amount of material handling, accelerating the construction progress. (4) Reduces overall costs: Material savings, improved labor efficiency, and shortened construction period work together to significantly reduce the overall project cost.
[0024] The cement-based grouting material provided in this application has excellent early strength and controllable workability, ensuring convenient construction and quality: (1) Good workability retention: The reasonable combination of retarder and accelerator ensures that the grout maintains high fluidity and operability within the time required for construction. (2) High fluidity: Under the action of water-reducing agent, high fluidity can be achieved even at high water-to-material ratio, which is conducive to the self-leveling of the grout, full filling of gaps, and reduction of manual intervention. (3) Good early strength: The fast-hardening cement matrix and accelerator ensure that the material can build up strength quickly and shorten the time for opening to traffic.
[0025] The cement-based grouting material provided in this application forms a dense microstructure, giving it excellent volume stability and mechanical properties: (1) Improved durability: Low shrinkage, high density, and high bond strength effectively reduce problems such as cracking, hollowing, and peeling, extending service life. (2) Guaranteed final quality: High flatness and low cracking risk are key indicators of high-quality flooring. (3) Adaptable to harsh applications: Excellent mechanical properties are the basis for application in semi-flexible pavements and other scenarios subject to dynamic loads.
[0026] The high water-to-strength properties provided in this application perfectly meet the key requirements of semi-flexible pavement structures: First, the high water-to-material ratio gives the grout excellent fluidity, allowing it to fully penetrate and fill the interior of the highly porosity asphalt matrix, forming a uniform and dense composite structure, which is the foundation for ensuring the overall performance of the pavement. Second, relying on the fast-setting and fast-hardening cement matrix and precise admixture control, the material can rapidly develop early strength, meeting the stringent construction period requirements of semi-flexible pavements that need to be opened to light traffic in a short period of time, significantly improving construction efficiency. Third, its excellent later-stage mechanical properties, especially its high flexural strength and the toughening effect brought by the latex powder, give the grout layer excellent resistance to dynamic loads, effectively resisting the stress of repeated vehicle rolling, significantly reducing the risk of grout layer breakage, and extending the service life of the pavement. At the same time, the low shrinkage characteristics of the material ensure a tight bond between the grout layer and the asphalt matrix, avoiding voids or cracks caused by volume changes, and maintaining the integrity of the pavement structure. Finally, the good wear resistance of the hardened grout ensures the durability of the pavement surface layer, meeting the requirements for vehicle wear. Detailed Implementation
[0027] The present application will be further described in detail below with reference to embodiments, comparative examples and performance test results. These embodiments should not be construed as limiting the scope of protection claimed in this application.
[0028] Latex powder (VAE ELOTEX VAE 60W redispersible latex powder) and defoamer (German Mingling P803 defoamer) were purchased from Shanghai Zengye Industrial Co., Ltd.; ethylene-vinyl acetate copolymer was purchased from Shanghai Yuanye Biotechnology Co., Ltd.; the remaining raw materials were all available through commercial purchase. Example
[0029] Examples 1-5 Examples 1-5 provide a cement-based grouting material and its preparation method, respectively.
[0030] The difference in the above embodiments is that the amounts of cement, anhydrite powder, and slag powder in the cement-based grouting material are different, as shown in Table 1.
[0031] The preparation method of the cement-based grouting material in the above embodiments is as follows: The preparation method of the coagulant is as follows: 25g of calcium carbonate and 90g of alumina after being sieved through 100 mesh are mixed and stirred to obtain a solid material. 10% distilled water is added and stirred thoroughly. Then 7g of ethylene-vinyl acetate copolymer (vinyl acetate content is 28wt%, melt index is 25g / 10min) is added and stirred thoroughly. The mixture is kept under a pressure of 40kN for 35s. The prepared sample is dried to constant weight and ball-milled through a 100-mesh sieve to obtain the coagulant. The weight ratio of calcium carbonate, alumina and ethylene-vinyl acetate copolymer is 2.5:9:0.7.
[0032] According to Table 1, weigh the corresponding weights of each raw material component, and mix the white crack-resistant, fast-setting, and quick-hardening high-belite sulfoaluminate cement 42.5, anhydrite powder, S95 grade blast furnace granulated slag powder, heavy calcium carbonate powder, graded fine aggregate (composed of 100-mesh dolomite sand and 40-mesh dolomite sand in a weight ratio of 2:1), polycarboxylate superplasticizer, HPMC thickener, defoamer, hydroxyethyl cellulose, latex powder, tartaric acid retarder, and accelerator evenly to obtain a dry powder material; add water and mix evenly to obtain the cement-based grouting material.
[0033] Table 1. Dosage of each component in the cement-based grouting materials of Examples 1-5 and Comparative Examples 1-2. Examples 6-7 Examples 6-7 respectively provide a cement-based grouting material and its preparation method.
[0034] The difference between the above embodiments and Embodiment 1 is that the types of graded fine aggregates are different, as detailed below.
[0035] In Example 6: the graded fine aggregate is composed of a mixture of 100-mesh dolomite sand and 40-mesh dolomite sand in a weight ratio of 1:2.
[0036] In Example 7: the graded fine aggregate is composed of a mixture of 100-mesh dolomite sand and 40-mesh dolomite sand in a weight ratio of 2.5:0.5.
[0037] All other process parameters in the above embodiments are the same as those in Embodiment 1.
[0038] Examples 8-12 Examples 8-12 provide a cement-based grouting material and its preparation method, respectively.
[0039] The difference between the above embodiments and Embodiment 1 is that the preparation method of the coagulant is different, as shown below.
[0040] In Example 8: In the preparation method of the coagulant, the performance parameters of the ethylene-vinyl acetate copolymer are: vinyl acetate content of 25wt% and melt index of 19g / 10min.
[0041] In Example 9: In the preparation method of the coagulant, the performance parameters of the ethylene-vinyl acetate copolymer are: vinyl acetate content of 28wt% and melt index of 32g / 43min.
[0042] In Example 10: In the preparation method of the coagulant, the weight ratio of calcium carbonate, alumina, and ethylene-vinyl acetate copolymer (vinyl acetate content of 28wt%, melt index of 25g / 10min) is 9:2.5:0.1.
[0043] In Example 11: In the preparation method of the coagulant, the weight ratio of calcium carbonate, alumina, and ethylene-vinyl acetate copolymer (vinyl acetate content of 28wt%, melt index of 25g / 10min) is 2:11:0.2.
[0044] In Example 12: In the preparation method of the coagulant, the weight ratio of calcium carbonate, alumina, and ethylene-vinyl acetate copolymer (vinyl acetate content of 28wt%, melt index of 25g / 10min) is 3:7:1.2.
[0045] All other process parameters in the above embodiments are the same as those in Embodiment 1.
[0046] Comparative Example Comparative Examples 1-2 Comparative Examples 1 and 2 respectively provide a cement-based grouting material and its preparation method.
[0047] The difference between the above embodiments and Embodiment 1 is that the amounts of cement, anhydrite powder, and slag powder in the cement-based grouting material are different, as shown in Table 1.
[0048] All other process parameters in the above comparative examples are the same as those in Example 1.
[0049] Comparative Examples 3-5 Comparative Examples 3-5 each provide a cement-based grouting material and its preparation method.
[0050] The difference between the above comparative example and Example 1 is that the preparation method of the coagulant is different, as shown below.
[0051] In Comparative Example 3: The preparation method of the coagulant did not include ethylene-vinyl acetate copolymer. Specifically, 25g of calcium carbonate and 90g of alumina after being sieved through 100 mesh were mixed and stirred to obtain a solid material. 10% distilled water was added and stirred thoroughly. The mixture was kept under a pressure of 40kN for 35s. The prepared sample was dried to constant weight and then ball-milled through a 100-mesh sieve to obtain the final product.
[0052] In Comparative Example 4: In the preparation method of the coagulant, an equal amount of aluminum sulfate was used instead of aluminum oxide.
[0053] In Comparative Example 5: In the preparation method of the coagulant, an equal amount of ethylene alcohol-ethylene copolymer (purchased from Merrill, CAS No.: 25067-34-9, product number: M87799) was used instead of ethylene-vinyl acetate copolymer.
[0054] All other process parameters in the above comparative examples are the same as those in Example 1.
[0055] Performance testing (1) Compressive strength and flexural strength: According to GB / T 50448, the compressive strength and flexural strength of cement-based grouting materials shall be determined.
[0056] (2) Shrinkage: The 28-day free expansion rate of cement-based grouting materials was determined according to the provisions of JC / T 986.
[0057] (3) Abrasion resistance: The abrasion resistance of cement-based grouting materials shall be determined in accordance with the provisions of JC / T 986.
[0058] Test results are shown in Table 2.
[0059] Table 2. Performance test results of cement-based grouting materials in the examples and comparative examples. As can be seen from the test results in the table above, the cement-based grouting material prepared using the technical solution provided in this application, under the condition of a high water-to-material ratio, not only maintains excellent construction fluidity and exhibits excellent performance in rapidly developing early strength and significantly improving later compressive and flexural strength, but also has excellent low shrinkage and wear resistance.
[0060] Comparing the test results of Examples 1-5 and Comparative Examples 1-2, it can be seen that the dosage of each raw material component—cement, anhydrite powder, and slag powder—has a significant impact on the performance of cement-based grouting materials. In Comparative Examples 1-2, the dosages of cement, anhydrite powder, and slag powder as cementitious materials were mismatched, resulting in cement-based grouting materials with poor overall performance. In contrast, this application, by using a cementitious material composed of specific dosages of high-belite sulfoaluminate cement, anhydrite powder, and slag powder, combined with graded fine aggregates, fillers, and functional admixtures, ensures the overall performance of the cement-based grouting material.
[0061] By comparing the test results of Examples 1, 8-12, and Comparative Examples 3-5, it can be seen that the accelerator preparation method in Comparative Example 3 did not add ethylene-vinyl acetate copolymer; the accelerator preparation method in Comparative Example 4 used an equal amount of aluminum sulfate instead of alumina; and the accelerator preparation method in Comparative Example 5 used an equal amount of ethylene alcohol-ethylene copolymer instead of ethylene-vinyl acetate copolymer. The resulting cement-based grouting materials had poor overall performance. In contrast, this application uses calcium carbonate, alumina, and ethylene-vinyl acetate copolymer to prepare the accelerator, ensuring the overall performance of the cement-based grouting material. Furthermore, this application further improves the overall performance of the cement-based grouting material by optimizing the weight ratio of calcium carbonate, alumina, and ethylene-vinyl acetate copolymer.
[0062] Although the present invention has been described in detail above with general descriptions and specific embodiments, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention.
Claims
1. A cement-based grout material, characterized in that, Specifically include the following weight parts of components: high belite sulphoaluminate cement 25.2~35.0 parts, anhydrite powder 4.32~6.32 parts, slag powder 6.48~19.46 parts, heavy calcium powder 0~14.92 parts, graded fine aggregate 46.92~47.38 parts, water reducing agent 0.02~0.05 parts, thickening agent 0~0.6 parts, defoaming agent 0.03~0.2 parts, cellulose 0~0.17 parts, latex powder 1.0~2.5 parts, retarder 0.03~0.1 parts, accelerator 0.03~0.2 parts;Water material ratio is 0.30~0.43;The accelerator is prepared from calcium carbonate, aluminium oxide, ethylene-vinyl acetate copolymer.
2. Cement-based grout material according to claim 1, characterized in that Specifically include the following weight parts of components: high belite sulphoaluminate cement 27.2~32.0 parts, anhydrite powder 4.82~5.82 parts, slag powder 11.48~14.46 parts, heavy calcium powder 5~9 parts, graded fine aggregate 46.92~47.38 parts, water reducing agent 0.03~0.04 parts, thickening agent 0.2~0.4 parts, defoaming agent 0.09~0.14 parts, cellulose 0.06~0.12 parts, latex powder 1.5~2.0 parts, retarder 0.06~0.08 parts, accelerator 0.12~0.18 parts;Water material ratio is 0.34~0.
38.
3. Cement-based grout material according to claim 1, characterized in that The graded fine aggregate is composed of 80~120 mesh dolomite sand and 20~60 mesh dolomite sand with a weight ratio of 1.5~2.5:0.5~1.
5.
4. Cement-based grout material according to claim 1, characterized in that The graded fine aggregate is composed of 80~120 mesh dolomite sand and 20~60 mesh dolomite sand with a weight ratio of 1.7~2.2:0.7~1.
2.
5. The cement-based grout material of claim 1, wherein The preparation method of the accelerator is that: calcium carbonate and aluminium oxide are mixed and stirred to obtain solid material, 8~12% distilled water is added and fully stirred uniformly, then ethylene-vinyl acetate copolymer is added, fully stirred uniformly, and then baked for 25~50 s under a pressure of 30~50 kN, and then dried to constant weight, and ball milled to obtain the accelerator.
6. Cement-based grout material according to claim 5, characterized in that In the preparation method of the accelerator, the weight ratio of calcium carbonate, aluminium oxide and ethylene-vinyl acetate copolymer is 2~3:7~11:0.2~1.
2.
7. Cement-based grout material according to claim 6, characterized in that In the preparation method of the accelerator, the weight ratio of calcium carbonate, aluminium oxide and ethylene-vinyl acetate copolymer is 2.2~2.8:8~10:0.5~0.
9.
8. Cement-based grout material according to claim 5, characterized in that The performance parameters of the ethylene-vinyl acetate copolymer are that: the vinyl acetate content is 25~30 wt%, and the melt index is 15~30 g / 10 min.
9. The cement-based grout material of claim 1, wherein, The water reducing agent is polycarboxylic acid water reducing agent;The thickening agent is HPMC;The defoaming agent is German Mingling P803 defoaming agent AGITAN powder defoaming agent;The cellulose is hydroxyethyl cellulose;The latex powder is VAE glue powder;The retarder is selected from one or more of sodium gluconate and tartaric acid.
10. The method of preparing a cement-based grout material according to any one of claims 1 to 9, characterized in that, Specifically comprising the following steps in sequence: weighing respective weights of each raw material component respectively, mixing high belite sulphoaluminate cement, anhydrite powder, slag powder, heavy calcium powder, graded fine aggregate, water reducing agent, thickening agent, defoaming agent, cellulose, latex powder, retarder, accelerator uniformly to obtain dry powder material; adding water, mixing uniformly, to obtain the cement-based grouting material.